EFEKTIFITAS PERAN DAN FUNGSI CASE MANAGER DALAM MENINGKATKAN MUTU ASUHAN KEPERAWATAN DI RUANG RAWAT INAP RSU MK DAN RSU KB - Noviani, Ratna Wulan Hardian; Muhammad Hadi; Rohadi Haryanto; Nursalam, Prayetni (Program Studi Akuntansi IKOPIN, 2021)
Case management is a strategy of interventions that used by health care systemsand providers to support clients, to coordinate health services, and facilitateresults, both in price and quality. The case manager is generally responsible forthe coordination and continuity of patient services or at certain services phasesclearly identified very close to the patient so that the case management model ledby the case manager is able to realize health services based on patient centeredcare. The Purpose: Knowing effectiveness role and function of case manager inimproving quality of nursing assessment in inpatient ward of MK and KB generalhospital. The method of this study: the method used is quantitative research methodusing Quantitative Experimental Design. There are two research groups namely the experimental that is given treatment and the control group as a comparison.Thenumber of samples in this study were 25 respondents for each group by collectingdata using a questionnaire. Statistical test used to determine the effectiveness ofvariables using the General Linear Model Reapeted Measure. The Results: theresults of the analysis show that there is an increase in the mean value for eachmeasurement and p value = 0,000 smaller than the value of α = 0,05. Theconclusion: The results of the analysis show that there are differences in theeffectiveness of the role and function of the case manager in improving the qualityof nursing assessment in the inpatient ward of MK general hospital.